Factors of Training Design and Training Facilities on Training Effectiveness at the Surakarta Vocational and Productivity Training Center - Cahyaningrum, Anisya; Waskito, Jati; Saputro, Edy Purwo; Kussudyarsana, (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
The study goals is to understand how facilities, research, and design influences training effectiveness at The Surakarta Vocational and Productivity Training Center. A sort of research as many as 96 respondents took part in this quantitative training at The Surakarta Vocational and Productivity Training Center. Primary data with measurement scales likert and data analysis using SPSS version 26 make up the research data sources. Dependent variables include the effectiveness of the training, whereas independent variables include the context, substance, and methodology of the training, as well as the competency of the trainers and the training facilities. According to the study's findings, (a) context, content, and material training are positively and significantly related to training effectiveness; (b) The method of training is The competency trainer is similarly positively and significantly connected to training effectiveness; (c) Training effectiveness is related to training effectiveness; (d)The training facilities are important to training efficacy and have a beneficial influence.